Spinal anesthesia in a patient on monoclonal antibody treatment: a poisoned chalice? A case report. Issue 9 (19th April 2021) - Herijgers, Anneleen; Van Dyck, Lisa; Leroy, Ilse; Dobbels, Laurens; Van de Putte, Peter B C
Abstract : Background: Paraplegia is a rare complication of spinal anesthesia. Case presentation: We report a case of a 68-year-old man who developed postoperative paraplegia and hypoesthesia after spinal anesthesia for an otherwise uncomplicated transurethral resection of the prostate. Acute transverse myelitis was diagnosed based on urgent MRI. A prior history of similar though less severe neurological symptoms after obinutuzumab treatment for follicular lymphoma suggested a potential causative role for obinutuzumab, a novel monoclonal antibody that has not been associated with such devastating neurological side effects yet. High-dose steroid treatment partially attenuated the symptoms, but debilitating hypoesthesia and motor deficit remained present 3 months postoperatively. Conclusion: The presented case warrants caution when performing neuraxial anesthesia in patients on monoclonal antibody therapies.